Uji Aktivitas Serum Anti Aging Ekstrak Daun Salam (Syzygium polyanthum) - Wahyu Purwanjani (Universitas An Nuur, 2023)
Background : Skin aging is a natural process characterized by a decrease in skin elasticity, firmness, and moisture, as well as the appearance of wrinkles caused by both intrinsic and extrinsic factors such as UV exposure and free radicals. The use of natural ingredients as anti-aging agents is increasingly being explored, one of which is bay leaf (Syzygium polyanthum), known to contain active compounds such as flavonoids, tannins, and antioxidants that can combat free radicals and slow down the skin aging process. Objective : To evaluate the anti-aging activity of a serum formulation containing bay leaf extract as the main ingredient. Method : Bay leaf extract was obtained through a maceration process and then formulated into a serum with various concentrations. The effectiveness test was conducted on rabbits using a Skin Analyzer device to measure skin parameters such as moisture, elasticity, and wrinkle depth before and after serum application. Results : The study showed that the serum containing 4.5% extract concentration provided the most significant improvement in skin condition, with notable increases in moisture and elasticity and a marked reduction in wrinkle depth. Therefore, bay leaf extract has potential as an active agent in anti-aging skincare products.